2013
DOI: 10.1186/2193-1801-2-542
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of one step nucleic acid amplification (OSNA) whole node assay in sentinel lymph node (SLN) analysis in breast cancer

Abstract: BackgroundThe purpose of this study is to present our first results of sentinel node analysis (SLN) by one step nucleic acid amplification (OSNA) in routine clinical practice in our centre and compare them with the results of classic histopathological analysis in a historical cohort from our same institution.Methods407 patients (total study population) with early breast cancer and no clinical nodal involvement underwent SLN biopsy in our institution. The SLN was analysed by OSNA in 164 biopsies. OSNA results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
2
8
1
Order By: Relevance
“…Ruano et al [ 24 ] also confirmed that whole lymph node examination by means of OSNA assay detects more metastases than standard histopathological study. These results were consistent with data reported by Santaballa et al [ 22 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Ruano et al [ 24 ] also confirmed that whole lymph node examination by means of OSNA assay detects more metastases than standard histopathological study. These results were consistent with data reported by Santaballa et al [ 22 ].…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have reported that the classical histopathological analysis of SLNs significantly underestimates the axillary staging of breast carcinoma in comparison with molecular studies of SLNs by OSNA [ 8 , 22 , 23 ]. Ruano et al [ 24 ] confirmed this finding in a large study comparing the use of OSNA and histopathology for staging of axillary lymph nodes in breast cancer patients with positive SLNs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, postoperative assessment using the FFPE LNs is preferable to the intraoperative pathological examination, although a significant proportion of patients who are assessed postoperatively as having SLN metastasis need to undergo the second surgery for cALND. However, OSNA renewed our interest in intraoperative assessment of SLNs, since OSNA has been repeatedly shown to be at least as accurate as histological examination, including immunohistochemistry, using the FFPE LNs, 21 , 22 and better than frozen section examination or imprint cytology. 21 , 23 These results point to the possibility that an intraoperative prediction model for NSLN metastasis as good as the postoperative prediction model can be constructed if OSNA is incorporated in the model.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid sampling errors, the concept of whole SLN analysis was reported as standard technique. 19 It also shows a quantitative result of the TTL. [22][23][24][25] Several studies have reported on significant predictive factors of additional non-SLN metastasis in patients with positive SLN who met the ACOSOG Z0011 trial but may not have completely met all the criteria of the research study.…”
Section: Discussionmentioning
confidence: 94%